THE KAZAKH FOLK FUNERAL CUSTOM OF ‘DAVRA’ (Journal of history, 2025)
This article contains an analysis of Kazakh custom of ‘daure’ (davra), that referred to cycle of funeral rituals. This custom was quite well described in the second half of the 19th century and was designated as an original Islamic rite in the works of this period. In the XX century a number of studies are coming out, in that are indicated pre-Islamic origin of ‘daure’.The aim of article is to define whether custom of ‘daure’ determined by Islamic canons or this custom also related with pre-Islamic beliefs. The novelty of article consists in the application of a new analysis perspective of Kazakh rituals and beliefs from the point of ratio of Islamic and pre-Islamic elements. In the article it is proposed to refer this rite to a variant of synthesis of pre-Islamic and Islamic rituality.The essence of the rite is ‘transfer’ deceased people on other peoples, animals and objects of the material world. This concept was formed in the pre-Islamic epoch, then it was significantly rethought in the national consciousness and has come to be recognized as a native Islamic custom. Thus, this ritual included Islamic elements, such as redemption of wrongdoings for violating the canons of the Islamic faith, participation of mullah, reading a prayer.In whole, the researches in this field could help to reveal distinctive features of traditional and modern Kazakh religious worldview. The article consists of introduction, methods, results, discussion and conclusions of research.
Keywords: ritual of ‘davra’, rites of lifecycle, funeral rites, Islam, sharia’a, ritual of ‘davra’, pre-Islamic worldview traditions, mullah, ‘kaffara’, Phidias, magic, synthesis.